Review Of Main Land Facilities Needs In Marampa Flighting Port, West Papua Province - Brenhard Mangatur Tampubolon; Dahlia Dewi Apriani; M.Ridho Alfaridzi (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2021)
Marampa Ferry Port is a port located in Manokwari Regency, West Papua Province. This port serves as an access crossing between provinces and within provinces in West Papua. At the moment, it is still at the Marampa Ferry Terminal there are basic mainland facilities that are lacking or even non-existent, which can hinder port operations. To analyze this, an analysis is used based on the Decree of the Minister of Transportation Number KM.52 of 2004 concerning the Implementation of a Ferry Port for waiting room analysis, Regulation of the Minister of Transportation Number 103 of 2017 concerning the Regulation of Vehicles Using Crossing Transportation Services and Decree of the Director General of Land Transportation Number: SK.242 / HK.104 / DRJD / 2010 Regarding Traffic Pattern Management for weighbridge analysis and gangway analysis which is based on the Regulation of the Director General of Land Transportation Number: SK.2681 / AP.005 / DRJD / 2006 Regarding Operation of Crossing Ports. Therefore, it is necessary to have a review and additions to some facilities that are lacking or even non-existent at the Marampa Port, this is done to improve the existing services at the Marampa Ferry Port. Improvement of main land facilities such as repairing waiting rooms and additional supporting facilities such as air conditioning, television, charger boxing and wifi access, providing weigh bridges, and gangways that go directly to the ship deck are carried out to facilitate port operational activities so that passengers can experience the excellent service provided by the port.